PEMIKIRAN POLITIK ABU A’LA ALMAUDUDI - Chindi Ayu Shonia; Lia Hermawati (ISTIGHNA: Jurnal Pendidikan dan Pemikiran Islam, 2020)
Studying Islam and its political affiliation in the Islamic world is one of the most never-ending studies. Various theories that have been introduced and introduced by various scholars from the early medieval period to the modern intellectuals of the West, though they are not very convinced of Islam, are also involved in the search for a new formula for the nature of the attitude. should be Islamic religion and politics. This article will examine the political views of Abu a'la Al Maududi, a leading figure, a Muslim political thinker from Pakistan who introduced a synthesis to reconcile Western secular democracy with the concept of Islamic theocracy.